HEALTH COURSE STUDENTS’ KNOWLEDGE ABOUT HEMATOPOIETIC STEM CELL DONATION - Indyara de Sá Silva, Dayane; Leonardo de Oliveira Dias, Cristiano; Di Pietro Carvalho, Renata; Geovanna Santos Leopoldo, Anielly; Dias Souto, Viviane; de Souza Oliveira, Karoline; Loreddany Santos Queiroz e Silva, Priscilla; Nunes de Aquino Fonseca, Euvaíra; Aparecida Alves Barbosa, Romana; de Oliveira Neto Silva, Suede; Rodrigues Pereira, Carla; Lima Silva de Abreu, Letícia; et al. (Health and Society, 2026)
Objective: To analyze the knowledge of health sciences students about bone marrow transplantation and the National Registry of Voluntary Bone Marrow Donors (REDOME). Methods: Cross-sectional study conducted with 205 students from higher education institutions located in the north of Minas Gerais. Students’ knowledge about leukemia, bone marrow donation and REDOME registration was measured using an online questionnaire. Data were analyzed using descriptive statistics and Person’s chi-square test was applied to assess the correlation between the studied estimates. Results: Participants were divided into 155 (75.6%) female students and 50 (24.4%) male students, with a mean age of 23.6 years. It is noteworthy that most of the assessed group reported no or poor knowledge about bone marrow donation. Female gender (p=0.018), registered donors at REDOME (p=<0.005) and students with knowledge about leukemia treatment (p=0.000), were associated with better knowledge indexes about hematopoietic stem cell donation. Conclusion: The results of this study attest to the need to educate health students about the bone marrow donation process and REDOME.